THE ASSESSMENT OF RHEOLOGICAL QUALITIES WITH THE MIXOLAB OF DIFFERENT WHEAT FLOURS ENRICHED WITH THEIR BRAN - Xhabiri, Gafur; Acoski, Toni; Stanojeska, Marija; Sinani, Valbona (European Scientific Journal, ESJ, 2013)
The increasement range of products with high dietary value of cereals, particularly bread, takes an important place in the contemporary bread making. Bread is basic food in the Balkan region and as such it can be used efficiently to reduce the deficit of some nutrients, especially of dietary fibers. Precisely wheat bran as a milling by-product is important for the nutritional values, since they contain dietary fibers, minerals, proteins with high nutritional value, etc. Taking in consideration these reasons the addition of wheat bran in bread production will increase the nutritional value of bread, but it will also influence the technological qualities of dough, especially the rheological qualities. From the obtained results with Mixolab, we can note that the water absorption increases with the increasing addition of wheat bran, as well as the dough stability increases too, but the mixture of wheat Novosadka rana 2 has much better quality than the others. The values of C1 and C2 are increasing with the wheat bran addition, while the values of C3, C4 and C5 are reducing with the addition of wheat bran.